SIKAP FOLLOWERS REMAJA PEKANBARU TERHADAP AKUN INSTAGRAM @AWKARIN - Vetty Anggraeni (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2020)
One of the Indonesian celebrities in Instagram, Karin Novilda, has an Instagram social media account @awkarin which has four million followers. In the Instagram account, there are 6.916 photos and videos with phonographical content followed by young people. The Instagram account @awkarin was reported to the Indonesian Child Protection Commission (KPAI) on complaints from representatives of Indonesian parents who were worried about the existence of the Instagram account. Awkarin is deemed inappropriate to upload pornographic content on his Instagram account because it can have a negative impact on young people. The research objective is to examine more deeply the perceptions of Pekanbaru teenagers who follow the @awkarin Instagram account. The researcher refers to the S-O-R theory by Burhusm Frederic Skinner using qualitative methods with in-depth interviews with ten informants, observation and documentation. The results showed that the teenagers in Pekanbaru did not follow a lifestyle like Awkarin but only liked the style of taking pictures, style of dress and looking for important information in the Instagram account.